Principle and Design of Chirped Fiber Grating. (October 2020) - Mao, Yan; Yan, Xingpeng; Wang, Weifeng
Abstract: At present, as a feasible solution to the dispersion problem in optical fiber communication, chirped fiber grating has been widely used and concerned. This paper analyzes the principles of linear chirped fiber gratings and nonlinear chirped fiber gratings, and on the basis of summarizing the current design of chirped fiber gratings, two implementation methods of chirped fiber gratings are proposed.